Harnessing AI for Writing Excellence: Exploring ToolBaz.com and Gender Differences in Enhancing Twelfth Graders' Narrative Skills - Wiji Kholifah; Hamzah Hamzah (STAI Hubbulwathan Duri, 2025)
This study investigates the effectiveness of ToolBaz.com, an AI-based writing tool, in enhancing narrative text writing skills among grade XII students at SMAN 3 Padang, Indonesia. Given the increasing integration of AI in education, this research aims to determine whether AI-assisted writing tools improve student performance compared to traditional methods. A quasi-experimental design was employed, involving an experimental group that used ToolBaz.com and a control group using a non-AI tool. Writing performance was assessed through pre- and post-tests. Data were analyzed using an independent t-test and two-way ANOVA to measure the tool's impact and gender-based differences. Findings indicated a statistically significant improvement in writing scores in the experimental group (M = 80.12) compared to the control group (M = 75.37, p = 0.032). Additionally, the experimental group exhibited a lower standard deviation, suggesting more consistent learning outcomes. Gender-based analysis showed no significant differences, indicating that ToolBaz.com provides equal support for both male and female students. The results suggest that AI-based tools can enhance writing performance by offering personalized scaffolding and structured feedback, leading to more effective learning. The consistency in learning outcomes further highlights AI's role in reducing disparities in writing proficiency. AI-assisted writing tools have the potential to revolutionize writing instruction in secondary education. Further research, including longitudinal and qualitative studies, is recommended to assess long-term effects and students' perceptions of AI-based learning interventions.